2016
DOI: 10.1016/j.healthpol.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the 2011 Reimbursement Act in Poland: Desired and undesired effects of the changes in reimbursement policy

Abstract: The Act of 12 May 2011 on the Reimbursement of Medicines, Foodstuffs Intended for Particular Nutritional Uses and Medical Devices constitutes a major change of the reimbursement policy in Poland. The main aims of this Act were to rationalize the reimbursement policy and to reduce spending on reimbursed drugs. The Act seems to have met these goals: reimbursement policy (including pricing of reimbursed drugs) was overhauled and the expenditure of the National Health Fund on reimbursed drugs saw a significant dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In their daily operations, health technology assessment (HTA) bodies make decisions or recommendations involving patients’ lives and large sums of public money. Given the many interests this inevitably attracts, and the global trends towards evidence-based policymaking and good governance, it is unsurprising that transparency has been a long established principle of good practice in HTA (Drummond et al ., 2008). Notably, it is part of the mission and value statement of the European Union network for Health Technology Assessment (2017), and has been put forward as a solution to the less-than-perfect utilisation of HTA by decision-makers (Sorenson et al ., 2008) or the low acceptance of its outputs by the public and stakeholders (Panteli et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In their daily operations, health technology assessment (HTA) bodies make decisions or recommendations involving patients’ lives and large sums of public money. Given the many interests this inevitably attracts, and the global trends towards evidence-based policymaking and good governance, it is unsurprising that transparency has been a long established principle of good practice in HTA (Drummond et al ., 2008). Notably, it is part of the mission and value statement of the European Union network for Health Technology Assessment (2017), and has been put forward as a solution to the less-than-perfect utilisation of HTA by decision-makers (Sorenson et al ., 2008) or the low acceptance of its outputs by the public and stakeholders (Panteli et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Thus, it is suggested that medical management departments reconsider the necessity and accuracy for choosing the stage of disease and complications as the first and second subgroup factors in DRGs grouping of the area. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[20] While since the length of hospital stay is comparatively fluctuant, and that the control of hospitalization expenses is stricter that draws greater attention in China, we select inpatient medical expenditures as the statistical classification index to indicate the results of DRGs grouping in the study. [21] Nevertheless, the length of hospital stay is still one of the crucial factors affecting inpatient medical expenditures. Although setting the length of hospital stay as an independent variable will be helpful in explaining the linear equation toward hospitalization expenses, it is a form of medical output that can neither be adopted in the analysis of medical expenditure structure nor be used as the classification node.…”
Section: Discussionmentioning
confidence: 99%